Effects of molecular architecture of photoreactive phospholipid polymer on adsorption and reaction on substrate surface under aqueous condition. Issue 4 (4th November 2020) - Ishihara, Kazuhiko; Suzuki, Kohei; Inoue, Yuuki; Fukazawa, Kyoko
Abstract: Water-soluble photoreactive polymers with both phosphorylcholine and benzophenone groups were synthesized for the reaction between the polymers and the substrate in aqueous medium. To control the polymer architecture, the living radical polymerization method was applied to the copolymerization of 2-methacryloyloxyethyl phosphorylcholine and benzophenone methacrylates. These polymers possess various architectures, such as linear polymers, polymers with hydrophobic terminals, and 4-armed star-like polymers, that could promote their adsorption on the substrate surfaces. Additionally, two types of benzophenone groups were examined. Due to the bulky phosphorylcholine group, tetra(ethylene oxide) group as a spacer between polymer main chain and benzophenone group was considered. These polymers could adsorb on the surface in an aqueous medium, followed by reaction on the surface via photoirradiation depending on the chemical structure of the benzophenone group. The thickness of the polymer layer depended on the polymer architecture, i.e. a polymer with a hydrophobic terminal could form a thick layer. After modification, the contact angle by air in the aqueous medium decreased, compared to that on the base substrate. This was due to the hydrophilic nature based on the phosphorylcholine groups at the surface. The amount of proteins adsorbed on the surface also decreased because of the surface modification. These findings indicated that these water-soluble photoreactive polymers could be applied for the safer and effective surface modification of substrates via conventional photoirradiation without using an organic solvent.